2010
DOI: 10.1097/sle.0b013e3181cded54
|View full text |Cite
|
Sign up to set email alerts
|

Work-related Musculoskeletal Disorders When Performing Laparoscopic Surgery

Abstract: This study revealed musculoskeletal disorders in a majority of laparoscopists. The laparoscopic technique often requires static and tiring work positions, sometimes extreme, which can explain musculoskeletal disorders among general surgeons and gynecologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 18 publications
4
63
2
4
Order By: Relevance
“…Like Stomberg et al (2010), we found that females were much more likely to suffer musculoskeletal distress than their male colleagues [1]. This difference in prevalence between the sexes has been attributed to the fact that women have a lower muscle mass in the upper extremities when compared with men.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Like Stomberg et al (2010), we found that females were much more likely to suffer musculoskeletal distress than their male colleagues [1]. This difference in prevalence between the sexes has been attributed to the fact that women have a lower muscle mass in the upper extremities when compared with men.…”
Section: Discussionmentioning
confidence: 66%
“…The degree of instruction and knowledge on the ergonomics of gynaecological endoscopic surgery 3. The prevalence/frequency 1 and sites of possible musculoskeletal distress suffered and the requirement for treatment of such injury…”
Section: Survey Designmentioning
confidence: 99%
See 1 more Smart Citation
“…From an "e-mail" study of 317 laparoscopic surgeons in North America reported by Park et al, 272 (86.9%) of those performing such surgery reported physical symptoms of discomfort. This compares to the 20% to 30% incidence rate of occupational MSDs reported while performing traditional open surgery [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…MSDs are important occupational health problems, especially for medical and dental surgeons due to static posture, repetitive movements, forceful exertions and precise hand and wrist movement during surgery [8,9].…”
Section: Discussionmentioning
confidence: 99%